Tipping and residential segregation: a unified schelling model - Junfu Zhang (Institute for the Study of Labor (IZA), 2009)
This paper presents a Schelling-type checkerboard model of residential segregation formulated as a spatial game. It shows that although every agent prefers to live in a mixed-race neighborhood, complete segregation is observed almost all of the time. A concept of tipping is rigorously defined, which is crucial for understanding the dynamics of segregation. Complete segregation emerges and persists in the checkerboard model precisely because tipping is less likely to occur to such residential patterns. Agent-based simulations are used to illustrate how an integrated residential area is tipped into complete segregation and why this process is irreversible. This model incorporates insights from Schelling's two classical models of segregation (the checkerboard model and the neighborhood tipping model) and puts them on a rigorous footing. It helps us better understand the persistence of residential segregation in urban America.
Keywords: C72; C73; D62; R13; 330; Residential segregation; tipping; checkerboard model; Segregation; Wohnstandort; Agent-based Model; Spieltheorie; Theorie